The Effect of Liquidity Risk and Credit Risk on the Bank Performance: Empirical Evidence from Iraq - Al-Husainy, Noor Hashim Mohammed; Jadah, Hamid Mohsin (iRASD Journal of Economics, 2021)
The main objective of this paper is to study the effect of liquidity risk and credit risk on the profitability of commercial banks in Iraq. The sample is 18 private commercial banks listed in Iraqi Stock Exchange for six years for the period 2010 to 2020. This paper especially focuses on Iraqi commercial private Banks. The dependent variable is bank performance is measured by return on asset (ROA) and independent variables are, liquidity risks, credit risks. This paper employs a dynamic panel model, using Generalized Methods of Moments (GMM) panel data regression of Fixed-effects models. Furthermore, the findings illustrate that liquidity risk has a positive significant association with bank profitability. Meanwhile, credit risk has an adverse significant association with bank profitability. This paper contributes to the debate of risk management as well as determinants of bank performance from several dimensions. First, this study is the first to investigate the impacts of liquidity risks on bank performance in Iraq. Secondly, this is the first study that investigates the impacts of credit risks on bank performance in Iraq. It is hoped that the result of this paper can fill the gap of the literature on the association between liquidity risks, credit risks, and bank performance.